Creating a Twenty-First Century Public Utility Commission - Scott,Inara (2013 Western Academy of Legal Studies in Business Conference Proceedings, 2013)
Climate change and efforts to address it have put the electric utility system is under increasing pressure. New policy activities include efforts to increase the penetration of renewable resources, update aging transmission and distribution system infrastructure and transition to a more distributed generation model. Key to the success of these initiatives will be the support of public utility commissions—the state agencies that oversee retail electric utilities. In an effort to determine how these commissions will make decisions, this article explores the history, enabling legislation, and jurisdiction of commissions. It concludes that the authority and purpose of commissions has been narrowly interpreted to focus almost exclusively on short-term rate impacts to utility customers. As a result, efforts to reduce greenhouse gas emissions, modernize or transform the grid, or expand the path for new technologies such as electric vehicles, will not come from commissions, and in fact may be blocked by the same. Accordingly, the article offers options for modernization, ultimately recommending a melding of economic and environmental goals through a long-term planning process that balances cost and risk, yet remains squarely within the jurisdiction and historical purpose of the regulatory commission.
Keywords: Business Law